Rancang Bangun Alat Ukur Unting-unting Digital dan Waterpass Digital dengan Accelero Sensor Berbasis Mikrokontroler ATmega8 - Hidayat Nur Isnianto; Ali Ridho (Jurnal Rekayasa Elektrika, 2013)
Measurement process of concrete mold erectness (bekesting) and the floor slope was generally conducted using conventional method applying a plummet (pendulum) for bekesting erectness and waterpass for the floor slope. The drawbacks of this method are it requires a relatively longer processing time and the outcome of the slope measurement is not represented in degrees. The measurement of digital plummet and digital waterpass is easier as the measurement time is relatively short and the tilt angle is represented in degrees. This paper describes a design and implementation of digital plummet and waterpass using Accelero Sensor MMA 7361L based on microcontroller ATmega8. The Accelero sensor MMA 7361L was used to read the tilt axis x, y, and z with analog voltage output that is converted into digital form using the ADC on the microcontroller. Based on the results of tools test for bekesting erectness and floor slope measurement, it was obtained that the average error were 0.51% and 0.49% for x-axis and y-axis respectively.